2009
DOI: 10.2340/00015555-0541
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin D Intake During Infancy Promote the Development of Atopic Allergy?

Abstract: The active metabolite of vitamin D, 1,25-(OH)2D3, has immunomodulatory properties in addition to its more established action on bone and calcium metabolism. Recently vitamin D has been proposed as one of several environmental factors responsible for the increase in atopic diseases during the last decades. The objective of this study was to determine whether the estimated dose of dietary vitamin D3 during the first year of life is associated with atopic diseases up to the age of 6 years. In a prospective birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
3
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(136 citation statements)
references
References 30 publications
5
120
3
8
Order By: Relevance
“…In a birth cohort study in Finland, subjects who had received vitamin D supplementation regularly during the first year compared to others had a marginally significantly increased risk of asthma at age 31 yrs [29]. Higher vitamin D intake at 5 months old was significantly positively related to the risk of eczema at the age of 6 yrs in Swedish children [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a birth cohort study in Finland, subjects who had received vitamin D supplementation regularly during the first year compared to others had a marginally significantly increased risk of asthma at age 31 yrs [29]. Higher vitamin D intake at 5 months old was significantly positively related to the risk of eczema at the age of 6 yrs in Swedish children [30].…”
Section: Discussionmentioning
confidence: 99%
“…Northern Finland study showed that children who received vitamin D supplements during infancy had a higher risk of developing asthma, atopy and allergic rhinitis in adulthood [41]. Similarly, Swedish study showed that higher intake of vitamin D in 1st year of life was associated an increased risk of developing atopic dermatitis by age 6 years [43].…”
Section: Conflicting Research Showing Reverse Causation With Normal /mentioning
confidence: 92%
“…65 Por outro lado, alguns autores defendem que o aumento da vitamina D estaria associada a recrudescimento de doenças alérgicas, e um estudo demonstrou que a suplementação em vitamina D durante a infância estaria relacionada a um risco 8 vezes superior de desenvolver dermatite atópica aos 6 anos. 66 Na morfeia e líquen escleroso a toma oral de vitamina D mostrou-se benéfica em vários casos, e foram reportados casos de tratamento eficaz com a aplicação tópica de calcipotriol.…”
Section: Níveis Adequados De Vitamina Dunclassified